Maritime Transportation System of Systems management framework: a System of Systems Engineering approach. (14th December 2009) - Mansouri, Mo; Gorod, Alex; Wakeman, Thomas H.; Sauser, Brian
This research develops an engineering approach that brings meaning to the context of Maritime Transportation System of Systems (MTSoS) and increases understanding of how to govern it more effectively. We suppose that: System of Systems (SoS) can be identified by its distinguishing characteristics; Maritime Transportation Systems (MTS) can be considered as a SoS in which constituencies seek their own goals; and its integrated objective is to transfer goods safely and efficiently. Based on these premises, we present our management framework. The proposed framework enables us to engineer and manage MTS more effectively from a System of Systems Engineering (SoSE) perspective.